2012
DOI: 10.2967/jnumed.112.103010
|View full text |Cite
|
Sign up to set email alerts
|

Breast Scintigraphy with Breast-Specific γ-Camera in the Detection of Ductal Carcinoma In Situ: A Correlation with Mammography and Histologic Subtype

Abstract: Ductal carcinoma in situ (DCIS) is a subtype of breast cancer encountered increasingly in clinical practice because of the widespread use of screening mammography. In the present study, we evaluated the usefulness of breast-specific g-camera (BSGC) scintigraphy in DCIS identification, describing the scintigraphic findings and their correlation with mammography and histologic subtype. Methods: Thirty-three women, aged 41-81 y, with surgically proven DCIS were retrospectively reviewed. Before surgery, all patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 18 publications
1
14
1
Order By: Relevance
“…In addition, the specificity for both groups was tempered by a relatively high number of false-positive results with 32.7% (50 of 153 lesions) and 35.9% (52 of 145 lesions) of findings representing false-positive outcomes in the low-dose and high-dose groups, respectively. The most common benign pathology resulting in a false-positive BSGI was fibrocystic change, which is consistent with prior studies reporting on false-positive lesions with BSGI (9,(22)(23)(24).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In addition, the specificity for both groups was tempered by a relatively high number of false-positive results with 32.7% (50 of 153 lesions) and 35.9% (52 of 145 lesions) of findings representing false-positive outcomes in the low-dose and high-dose groups, respectively. The most common benign pathology resulting in a false-positive BSGI was fibrocystic change, which is consistent with prior studies reporting on false-positive lesions with BSGI (9,(22)(23)(24).…”
Section: Discussionsupporting
confidence: 90%
“…Breast-specific gamma imaging has also shown utility in the diagnosis of DCIS with a sensitivity ranging from 67.0% to 94.0% (9,(23)(24)(25)(26). The reported sensitivity of mammography in the detection of DCIS ranges from 27% to 82% (26)(27)(28), while the sensitivity of MRI has been reported as 91.4% (29).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We could not compare pathologic subtypes and visibility on BSGI because our study included only a limited number of them, except IDC. Spanu et al [10] had reported a higher sensitivity to low-to-intermediate grade DCIS than to intermediate-to-high or high-grade DCIS (100% vs 91.3%), though the difference was not statistically significant. According to our results, 100% (12/12) of high-nuclear-grade cancers and 81% (34/42) of low-nuclear-grade were visible on BSGI, but without statistical significance.…”
Section: Discussionmentioning
confidence: 87%
“…The indocyanine green (ICG) added to 53 Furthermore, the incorporation of co-registered SPECT/CT to 3D navigation probe may be used during the operation offering a 3D roadmap to the surgeon and facilitating the anatomical localisation of SLN(s). In the current literature on radioguided surgery, this approach has been reported in penile cancer by Brower et al 54 In conclusion, the SLN procedure has widely been validated in vulvar cancer and cervical cancer.…”
Section: Advancements In Intraoperative Imaging and Instrumentationmentioning
confidence: 99%